THE EFFECT OF COMPENSATION AND JOB SATISFACTION ON TURNOVER INTENTION EMPLOYEES AT HOTEL LABERSA - Afriady Effendy; Nafiri Falah Agung; Hendri Herman (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of this research is to Influence Compensation and Job Satisfaction AgainstTurnover Intention Employees at Hotel Labersa. The population in this study were all employees at the Labersa Hotel as many as 115 respondents. The number of samples used in this study were 115 respondents. The research method used in this research is descriptive quantitative method.Based on the research that has been done at the Labersa Hotel, the following conclusions are obtained: VCompensation has a significant effect onturnover intention employees at Hotel Labersa with t count > t table (4.975 > 1.663) and a significant value of 0.000 <0.05; Job satisfaction has a significant effect onturnover intention employees at the Labersa Hotel with a t count > t table (3,500 > 1,663) with a significant value of 0,001 <0,05; Compensation and job satisfaction have a significant effect onturnover intention employees at Hotel Labersa with Fcount (3,100) > Ftable (2,386); Compensation and job satisfaction variables can explain the dependent variable, namelyTurnover Intention 71.1 percent while the remaining 28.9 percent is explained by other variables not observed in this study